Influence of Polymer Coatings on the Carrier Life Time in Solar Silicon Crystals - Steblenko, L P; Podolyan, A O; Korotchenkov, O O; Yashchenko, L M; Naumenko, S M; Kalinichenko, D V; Kobzar, Yu L; Kuryliuk, A M; Kravchenko, V M (Journal of Nano- and Electronic Physics, 2014)
Influence of polymer coatings on the photovoltage drop kinetics in solar Si crystals exposed to magnetic field action and X-ray irradiation is studied. The features found in the behavior of the electrophysical parameters suggest slowing down the photovoltage drop in the presence of polymer coatings at the surface of solar Si crystals. These features may be due to the influence of polymer coatings to reduce the concentration of recombination centers in crystals solar-Si.